2002
DOI: 10.1515/cclm.2002.195
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord and Maternal Blood Leptin Concentrations in Intrauterine Growth Retardation

Abstract: Leptin, the ob gene product, plays an important role in the regulation of body fat mass and weight. In previous studies, it was demonstrated that leptin is detectable in human fetal cord blood as early as at 18 weeks of gestation and that serum leptin concentrations are significantly reduced in small gestational age newborns. In the present study, we investigated whether umbilical and maternal serum leptin concentrations correlate with intrauterine growth retardation (IUGR). In addition, we aimed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 16 publications
5
50
1
1
Order By: Relevance
“…The leptin receptor is abundantly expressed in the arcuate nucleus of the hypothalamus [32] and this protein plays a crucial role in the endocrine regulation of appetite, energy homeostasis and insulin secretion. Interestingly, the changes seen in leptin gene expression oppose those seen in the concentration of leptin in cord blood of macrosomic infants, suggesting that the regulatory mechanisms involved in translating gene into protein expression are complex [30,33,34,35,36,37,38,39,40,41,42,43]. Leptin together with 10 other focused genes ( ATRX , CASP4 , FGF7 , FRZB , GCH1 , GFRA2 , GNGT1 , PHIP , PPIG , and SMC 3) are involved in a network that contributes to digestive system development and function; disturbance of this network suggests a higher risk for nutritional disease and behavioural disorders in macrosomic infants.…”
Section: Discussionmentioning
confidence: 99%
“…The leptin receptor is abundantly expressed in the arcuate nucleus of the hypothalamus [32] and this protein plays a crucial role in the endocrine regulation of appetite, energy homeostasis and insulin secretion. Interestingly, the changes seen in leptin gene expression oppose those seen in the concentration of leptin in cord blood of macrosomic infants, suggesting that the regulatory mechanisms involved in translating gene into protein expression are complex [30,33,34,35,36,37,38,39,40,41,42,43]. Leptin together with 10 other focused genes ( ATRX , CASP4 , FGF7 , FRZB , GCH1 , GFRA2 , GNGT1 , PHIP , PPIG , and SMC 3) are involved in a network that contributes to digestive system development and function; disturbance of this network suggests a higher risk for nutritional disease and behavioural disorders in macrosomic infants.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the human placenta (40) and other fetal tissues, including adipose, heart, and liver tissues (15), produce leptin. Cord blood leptin levels correlate with fetal size (20,27), and both placental and fetal leptin levels are decreased in pregnancies complicated by fetal growth retardation (18,39). However, PM appears to disrupt the relationship between cord leptin and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy neonates, cord blood levels of the hormone leptin are positively associated with birth weight (39), but the role of leptin in PM has not been examined. Leptin, which regulates appetite and metabolism, is produced by adipocytes, and leptin levels normally reflect body fat stores (21).…”
mentioning
confidence: 99%
“…Several studies demonstrated lower circulating leptin concentrations in IUGR neonates at birth, due to reduced fat mass (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) and/or decreased placental production (73)(74)(75). In some of these studies, fetal leptin levels per kilogram of fetal weight, as well as fetal leptin levels before 34 weeks of gestation, were not significantly different in IUGR, indicating that leptin secretion is mainly associated with adipose tissue accumulation (61)(62)(63)(64).…”
Section: The Role Of Adipose Tissuementioning
confidence: 99%
“…Although most studies suggest that fetal leptin levels are lower in IUGR (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), other investigators determined similar (80) and also higher (81) leptin concentrations. In this respect, a recent study from our group demonstrated lack of significant differences in fetal leptin concentrations between characteristic IUGR (birth weight!third customized centile) cases and appropriate-for-gestational-age (AGA) controls, possibly due to a more active production of leptin by visceral fat in the former (80).…”
Section: The Role Of Adipose Tissuementioning
confidence: 99%